GAMBARAN PENYESUAIAN DIRI PENYANDANG TUNADAKSA DI TEMPAT KERJA STUDI PADA PESERTA PELATIHAN DI BBRVBD CIBINONG - Faustine 2014070030; Penny Handayani (Universitas Katolik Indonesia Atma Jaya, 2019)
The increasing number of people with disabilities in Indonesia who are at work and still perceived as a burden on companies affect disability to work. This study focuses on participant who has physical disabilities because people with physical disability are the second most in Indonesia and their conditions of disability that can be seen directly, and cause psychological problems. As individuals, people with physical disabilities need to live independently, one of the ways to fulfill it by working. Physical disabilities will be in new environments and new situations. This requires adjustment so that eventually they can work productively. This research is using qualitative method using one on one interview. Three participants have attended training in BBRVBD Cibinong. This study use stage passed and the factors that influence their adjustment in the workplace. The results of this study indicate that the three participants experienced an emerging stage of stress at the beginning of work, defense mechanism, resolving problems, and after eight to ten months in the workplace, they are already in the adjustment stage. Three participants were influenced by five adjustment factors from Schneiders (1964). There are other factors that affect their adjustment, namely the perspective that physical disabilities has equal rights and opportunities at work. The desire to be independent, and prove to others who have to insult their physical condition.